Pengaruh amoniasi pith dengan urea terhadap nilai pakan dan pertambahan berat badan sapi peranakan ongole=Effect of Urea Ammoniation of Pith on Nutritive Value and Daily Weight Gain of Ongole Cattle - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT This experiment was conducted to evaluate the effect of urea ammoniation of pith on nutritive value, dry matter consumption and its effect on daily weight gain of Ongole cattle. The level of urea were use on: 0% (TO